PEMANFAATAN MEDIA PERMAINAN ULAR TANGGA BERANGKAS DALAM MENINGKATKAN KETERAMPILAN BERBICARA BAHASA INGGRIS PADA SISWA - Marina Tambunan (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2019)
The purpose of this study was to determine the use of media “Ular Tangga Berangkas” (Snake Stair Trimmer) Game in describing and improving the 4th-grade students’ English speaking skills. The study was conducted in Sekolah Dasar 16 of South Pontianak District. The method used in this study is a simple experiment that is applied in one experimental class. The snake stair trimmer game serves as a medium of learning the English language particularly in describing a person's physical description. Before using snake ladder trimmer media, the students' speaking skills in English only reached 29% above “Kriteria Ketuntasan Minimal/KKM” (minimum passing criteria). After using snake ladder trimming media, their speaking skills increased to 85% above KKM. Thus, the results of the study show that the media of snake ladder game has succeeded in increasing the competence of English speaking skills particularly in describing a person's physical description toward the 4th-grade students of SDN 16 South Pontianak.